The Clinical Implications of Aspergillus Fumigatus Sensitization in Difficult-To-Treat Asthma Patients - Mistry, Heena; Ajsivinac Soberanis, Hilda Maria; Kyyaly, Mohammad Aref; Azim, Adnan; Barber, Clair; Knight, Deborah; Newell, Colin; Haitchi, Hans Michael; Wilkinson, Tom; Howarth, Peter; Seumois, Grégory; Vijayanand, Pandurangan; et al. (The journal of allergy and clinical immunology in practice (Cambridge, MA), 2021)
Fungal sensitivity has been associated with severe asthma outcomes. However, the clinical implication of Aspergillus fumigatus sensitization in difficult-to-treat (or difficult) asthma is unclear. To characterize the clinical implications of A fumigatus sensitization in a large difficult asthma cohort. Participants who underwent both skin prick and specific IgE testing to A fumigatus (n = 318) from the longitudinal real-life Wessex AsThma CoHort of difficult asthma, United Kingdom, were characterized by A fumigatus sensitization (either positive skin prick test result or specific IgE) and allergic bronchopulmonary aspergillosis status using clinical/pathophysiological disease measures. A fumigatus sensitization was found in 23.9% (76 of 318) of patients with difficult asthma. Compared with A fumigatus nonsensitized subjects, those with sensitization were significantly more often male (50% vs 31%), older (58 years) with longer asthma duration (33 years), higher maintenance oral corticosteroid (39.7%) and asthma biologic use (27.6%), raised current/maximum log total IgE+1 (2.43/2.72 IU/L), worse prebronchodilator airflow obstruction (FEV 62.2% predicted, FEV /forced vital capacity 61.2%, forced expiratory flow between 25% and 75% exhalation 30.9% predicted), and frequent radiological bronchiectasis (40%), but had less psychophysiologic comorbidities. Allergic bronchopulmonary aspergillosis diagnosis was associated with higher treatment needs and stronger eosinophilic signals. Factors independently associated with A fumigatus sensitization in difficult asthma included maintenance oral corticosteroid use (odds ratio [OR], 3.34) and maximum log total IgE+1 (OR, 4.30), whereas for allergic bronchopulmonary aspergillosis included maintenance oral corticosteroid use (OR, 6.98), maximum log total IgE+1 (OR, 4.65), and radiological bronchiectasis (OR, 4.08). A fumigatus sensitization in difficult asthma identifies a more severe form of airways disease associated with greater morbidity, treatment need, and airways dysfunction/damage, but fewer psychophysiologic comorbidities. Screening of A fumigatus status should be an early element in the comprehensive assessment of patients with difficult asthma.